2018
DOI: 10.17014/ijog.5.3.221-234
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetostratigraphy and the Age of So’a Basin Fossil-Bearing Sequence, Flores, Indonesia

Abstract: Three fossil-bearing intervals have been recognized in the Pleistocene So'a Basin, with the upper one holding important evidence of hominin fossils. The sequence also contains numerous in situ stone artifacts and fossils of other vertebrate taxa. Therefore, multiple dating techniques are crucial to secure the age of the fossil and artifactbearing layers, especially the one with the hominin remains. This paper deals with the palaeomagnetic dating of the So'a Basin sequence to assist other dating methods that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…In addition, these WST ages are further supported by palaeomagnetic polarity data from both the Tangi Talo and Mata Menge sections, which indicate a clear polarity change from normal to reverse just below WST, consistent with the base of the Jaramillo normal subchron, dated at 1.07 Ma (see Fig. 2; Yurnaldi et al, 2018).…”
Section: Wolo Sege Tephrasupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, these WST ages are further supported by palaeomagnetic polarity data from both the Tangi Talo and Mata Menge sections, which indicate a clear polarity change from normal to reverse just below WST, consistent with the base of the Jaramillo normal subchron, dated at 1.07 Ma (see Fig. 2; Yurnaldi et al, 2018).…”
Section: Wolo Sege Tephrasupporting
confidence: 64%
“…At that time this boundary was thought to be 0.73 Ma, but is now considered to be 0.773 Ma (Cohen and Gibbard, 2019;Mark et al, 2017). These palaeomagnetic results have been confirmed in a more recent study (Yurnaldi et al, 2018), indicating that the base of MM-LOW is younger than 0.773 Ma (Fig. 2).…”
Section: Mata Menge Site Stratigraphysupporting
confidence: 52%
“…The Lower Fossil-bearing Interval (LFI), bracketed by a maximum age of 0.78 Ma based on palaeomagnetic evidence and a minimum age of 0.81 Ma [15,23], contains impoverished vertebrate fauna as well as in situ stone artefacts. The up to 2.2 m thick LFI represents a fining-upward sequence consisting of an amalgamated complex of sheets and lenses of sandstone alternating with tuffaceous siltstones and clay-rich mudflows.…”
Section: Stratigraphic Context For Mata Mengementioning
confidence: 99%
“…A Zircon Fission-track age of 0.80 ± 0.07 Ma for the Lower Fossil-bearing Interval (LFI) has been reported [13]. A more recent palaeomagnetic study [15] revealed that the LFI has a normal polarity and corresponds with the base of the Brunhes Normal Epoch. The LFI is therefore thought to be slightly younger than the Matuyama-Brunhes boundary at 0.773 Ma, which is within the error range of the ZFT age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation